Google Translate, ChatGPT or Google Bard AI: A Study toward Non-English Department College Students’ Preference and Translation Comparison - Hidayati, Niswatin Nurul; Nihayah, Dewi Hidayatun (Inspiring: English Education Journal, 2024)
The landscape of translation tools has evolved significantly, with an increasing reliance on artificial intelligence (AI) systems for various tasks. This study investigated the changing preferences among college students, especially those majoring outside of English departments, regarding the translation of abstracts from international journal articles. Besides, the authors also compared the translation results of Google Translate, ChatGPT and Google Bard AI. This research used qualitative research. The research results showed that the students prefer using AI such as ChatGPT or Google Bard AI. Moreover, whether the users used Google Translate, ChatGPT or Google Bard AI, the translation results showed that they were included in SL emphasis category.